HUBUNGAN MOTIVASI PERAWAT DAN GAYA KEPEMIMPINAN DENGAN PERILAKU PERAWAT DALAM PEMBUANGAN SAMPAH MEDIS BENDA TAJAM DI RSUD DR.A.DADI TJOKRODIPO KOTA BANDAR LAMPUNG - Rike Saputra; M. Arifki Zainaro; M. Ricko Gunawan (Malahayati Nursing Journal, 2020)
Introduction: sharp medical waste is not only able to cause scratch and stab wounds but also to infect wounds when they are contaminated by pathogen. A pre-survey result done by the researcher in wards of dr. A. Dadi Tjokrodipo at 20 January 2019 to 10 nurses concerning activities of nursing care and medicla waste management including needle, syringe, and bandage that were disposed without sorting.Objective: the objective of this research was to find out the correlations of nurse’s motivation and leadership style to nurse’s behavior in sharp medical waste disposal in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung. Method: this was a quantitative analytic survey research by using cross sectional approach and it was conducted in dr. A. Dadi Tjokrodipo public hospital from March to April 2019. Population was all nurses and samples were of total sampling. Data were collected by using questionnaires and analyzed by using univariate (frequency distribution) and bivariate (chi square test) analyses.Result: there were 31 respondents (54.4%) with poor medical waste littering behavior, 34 respondents (59.6%) with low motivation, and 29 respondents (50.9%) with bad leadership style. There were correlations of nurse’s behavior (p-value 0.000; OR 11.70) and leadership style (p-value 0.012: OR 4.725) to sharp medical waste disposal in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung in 2019. Conclusion: there were correlations of nurse’s motivation and leadership style to nurse’s behavior in littering sharp medical waste in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung in 2019. The researcher expects nurse’s motivation improvement concerning medical waste disposal by joining training about effects of improper sharp medical waste disposal.Introduction: sharp medical waste is not only able to cause scratch and stab wounds but also to infect wounds when they are contaminated by pathogen. A pre-survey result done by the researcher in wards of dr. A. Dadi Tjokrodipo at 20 January 2019 to 10 nurses concerning activities of nursing care and medicla waste management including needle, syringe, and bandage that were disposed without sorting.Objective: the objective of this research was to find out the correlations of nurse’s motivation and leadership style to nurse’s behavior in sharp medical waste disposal in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung. Method: this was a quantitative analytic survey research by using cross sectional approach and it was conducted in dr. A. Dadi Tjokrodipo public hospital from March to April 2019. Population was all nurses and samples were of total sampling. Data were collected by using questionnaires and analyzed by using univariate (frequency distribution) and bivariate (chi square test) analyses.Result: there were 31 respondents (54.4%) with poor medical waste littering behavior, 34 respondents (59.6%) with low motivation, and 29 respondents (50.9%) with bad leadership style. There were correlations of nurse’s behavior (p-value 0.000; OR 11.70) and leadership style (p-value 0.012: OR 4.725) to sharp medical waste disposal in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung in 2019. Conclusion: there were correlations of nurse’s motivation and leadership style to nurse’s behavior in littering sharp medical waste in dr. A. Dadi Tjokrodipo public hospital in Bandar Lampung in 2019. The researcher expects nurse’s motivation improvement concerning medical waste disposal by joining training about effects of improper sharp medical waste disposal.